KONTRIBUSI TENAGA KERJA WANITA DALAM BERUSAHATANI DI DESA PEGANTENAN KECAMATAN PEGANTENAN, KABUPATEN PAMEKASAN - Mohammad Shoimus Sholeh; Lia Kristiana; Maulidatul Hasanah (Jurnal MeA (Media Agribisnis), 2020)
Farming is an activity that is generally done by a man. Women as auxiliary workers who support the cultivation process. Women who work as farmers are indeed common and are mostly in rural areas. However, the contribution of women workers must be calculated in terms of time and income considering that in the process of cultivation many women workers are needed. The existence of female workers in Pegantenan Village makes it easy for farmers to carry out farming cultivation processes from pre-planting to post-harvest. Indirectly will contribute to family income. The purpose of this study was to analyze the decision-making factors in becoming a female labour and analyze the role and contribution of women farmers on household income. The analytical method used was  multiple linear regression analysis. The results showed that family income factors, the number of family dependents and the distance from the house to the rice fields influenced the decision of women to work in the process of crop cultivation. While the contribution of farm woman's income was 27.98% of the total household income.